Pengaruh Model Pembelajaran CORE Terhadap Kemampuan Koneksi Matematis Siswa: Studi Quasi Eksperimental: (The Effect of the CORE Learning Model on Students' Mathematical Connections Abilities: A Quasi-Experimental Study) - Widiastika, Neni; Kartika, Hendra; Hanifah, Hanifah (EDUPEDIA PUBLISHER, 2023)
Purpose: The primary objective of this study is to assess the level of achievement and improvement in students' mathematical connection abilities through the utilization of the CORE learning model. Methodology: The research employed a quasi-experimental approach, specifically the Non-equivalent Control Group Design. The target population for this study comprised all eighth-grade students from a junior high school in Karawang, West Java. Purposive sampling was employed to select two classes, namely Class VIII E and Class VIII F, to serve as the sample. Class VIII F was assigned as the experimental group. Each class consisted of 36 students. The quantitative data analysis was conducted using SPSS software version 24.0 for Windows. Findings: The results demonstrated that the average achievement of students' mathematical connections was superior in the group that received the CORE learning model compared to those who received conventional (direct) learning models. Moreover, the improvement in mathematical connection among students in the group that received the CORE learning model was higher than those in the conventional (direct) learning model group. This was substantiated by the Mann Whitney posttest analysis, yielding a significant value of 0.0075, as well as the Mann Whitney n-gain test, with a significant value of 0.0055. Significance: As the obtained significant value is less than α = 0.05, the null hypothesis (H0) is rejected, leading to the conclusion that the achievement and improvement of students' mathematical connection abilities using the CORE learning model were superior and more substantial compared to students utilizing conventional learning models.